Prevalence, Associated Factors and Awareness of Hypertensive Retinopathy among an Elderly Population with Hypertension in Nepal: The Bhaktapur Retina Study - Thapa, Raba; Khanal, Shankar; Tan, Hendra Stevie; Thapa, Suman Shumsher; van Rens, Gerardus Hermanus Maria Bartholomeus (Nepalese Journal of Ophthalmology, 2022)
Introduction: Hypertensive retinopathy is a common complication in patients with hypertension. This study aims to assess the prevalence, associated factors and awareness of hypertensive retinopathy among an elderly population with hypertension in Bhaktapur, Nepal.Materials and methods: This is a population-based, cross-sectional study conducted from 2013 to 2015 in Bhaktapur district, Nepal. The sample size was 2100 subjects aged 60 years and above.  From this sample, all diagnosed patients with hypertension were analyzed. A detailed history was obtained, and an ocular examination was performed. Results: Information was complete for 1860 (88.57%) subjects. The age of the study population ranged from 60 to 95 years with the mean age of 69.64±7.31 years. Hypertension was found in 643 subjects (34.61%), of which 224 (12.04%) were newly diagnosed cases.  Among the subjects with hypertension, hypertensive retinopathy was found in 81 cases (12.6%). Hypertensive retinopathy was more frequent in the age group 70-79 years (15.23%), males (13.25%), illiterates (13.56%), diabetics (16.49%), and body mass index (BMI) ≥25 kg/m2 (14%). None of the factors was found to be statistically significant. Among the study participants, awareness regarding the effect of hypertension on eye, retina and vision was found to be 13.84%, 8.4%, and 11.98% respectively. Conclusion: Prevalence of hypertension and hypertensive retinopathy among an elderly population of 60 years and above in Bhaktapur district, Nepal were similar to other countries. Hypertensive retinopathy was higher among males, illiterates, diabetes and BMI> 25kg/m2. Awareness of hypertensive retinopathy was 8.4% among hypertensive subjects. Emphasis should be directed toward improving awareness campaigns.